Ulnar Collateral Ligament Hybrid Reconstruction Surgery & Rehabilitation in the Overhead Athlete - Keith M Meister; Daniel Evans; Kevin E Wilk; Christopher A Arrigo (International Journal of Sports Physical Therapy, 2025)
Injuries to the ulnar collateral ligament (UCL), have become increasingly prevalent among overhead-throwing athletes, especially baseball pitchers. From 2011 to 2023, UCL injuries were the most common injury in Major League Baseball (MLB). Contributing factors include high pitching velocity, fatigue, overuse, and year-round pitching. Research indicates that 25% of MLB pitchers and 14% of Minor League pitchers have undergone UCL surgery, with these numbers steadily rising. After traditional UCL reconstruction, 83% of athletes return to the same or higher levels of play. While the success rate for UCL surgery is high, revision surgeries are becoming more frequent, with mixed outcomes. This underscores the need for improved surgical techniques and rehabilitation strategies. The hybrid UCL reconstruction technique presents a reliable and effective solution for treating UCL injuries, combining the benefits of autogenous grafting with internal brace augmentation. Current research, however, lacks focus on the surgical technique and rehabilitation following UCL hybrid surgery. Achieving successful outcomes with this procedure relies on a collaborative approach, from surgery to rehabilitation with adherence to the rehabilitation protocol and throwing program. Full recovery typically requires 12-14 months, depending on the athlete's level of play. With over 400 successful surgeries to date, this technique has proven to enhance stability and facilitate recovery, particularly in elite-level throwing athletes. The purpose of this paper is to describe this new surgical technique and its associated rehabilitation programs, emphasizing the importance of rehabilitation under the guidance of a rehabilitation professional experienced with overhead athletes.